2002
DOI: 10.4064/sm149-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Formulae for joint spectral radii of sets of operators

Abstract: The formula (M) = max{ χ (M), r(M)} is proved for precompact sets M of weakly compact operators on a Banach space. Here (M) is the joint spectral radius (the Rota-Strang radius), χ (M) is the Hausdorff spectral radius (connected with the Hausdorff measure of noncompactness) and r(M) is the Berger-Wang radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…In [25] the authors showed that the same is true if M is a precompact set of compact operators on a Banach space. In the further works [26,27,30] there were obtained several extensions of this result. Here we need the following consequence of [30,Theorem 4.11] (where only Banach algebras were considered).…”
Section: 7mentioning
confidence: 67%
“…In [25] the authors showed that the same is true if M is a precompact set of compact operators on a Banach space. In the further works [26,27,30] there were obtained several extensions of this result. Here we need the following consequence of [30,Theorem 4.11] (where only Banach algebras were considered).…”
Section: 7mentioning
confidence: 67%
“…A characteristic operator close to T e is the Hausdorff noncompactness measure T χ of the image of the unit ball X under the map T (recall that this is the greatest lower bound of the set of those ε > 0 for which T X has a finite ε-net and that T χ T e ). The advantage of the seminorm T χ is that it well agrees with the restriction of the operator to an invariant subspace and with its induced action on a quotient space (see, e.g., [17,Lemma 2.5]):…”
Section: Some Auxiliary Resultsmentioning
confidence: 98%
“…In [17], where formula (1.4) was proved for operators on any reflexive Banach space, we called it the generalized Berger-Wang formula, or the generalized BW-formula; but it shortly turned out that there are several types of formulas generalizing (1.3), and a more specific term is required. Note that (1.4) implies (1.3) for precompact families of operators of the form λ1 + K , where λ ∈ C and K is a compact operator; in [16] this observation served as a basis for the proof that any Lie algebra of Volterra operators has an invariant subspace.…”
Section: Introductionmentioning
confidence: 98%
“…In [ST02] the following extension of (1.1) to precompact sets of general (not necessarily compact) operators was obtained:…”
Section: Similarlymentioning
confidence: 99%